A tactical planning model for supply chains with nested ordering policy - Seyed Mehdi Zahraei (2012)
In this research, an integrated planning model is developed that incorporates the key tactical considerations in a supply chain, including safety stocks, production smoothing and reordering frequencies. The model characterizes a general network of stages that perform production and distribution functions in a multi-product environment. Each stage operates with a periodic review, nested base stock policy and that the stages are allowed to adopt different reorder intervals. Each production stage has a finite production capacity shared by the products it processes and produces a quantity according to a linear production function that characterizes its production smoothing behavior. Services from production stages and inventories are assumed to be guaranteed by performing expediting actions in times of capacity and inventory shortages. The model characterizes the expected total cost of the supply chain as functions of the planning parameters. The model is embedded into optimization procedures to determine the optimal planning parameters that minimize the expected total cost.